PENGEMBANGAN KEMITRAAN MASYARAKAT SEKITAR DALAM UPAYA MELINDUNGI DAN MENGAMANKAN KAWASAN DI KABUPATEN SANGIHE TALAUD - Mike Roring (EKOTON, 2012)
The objective of this research is trying to find out the possibility to use farm conserve system in villages around mountain in capital city of Kabupaten Sangihe Talaud, while the benefit of this research are to give contribution in science on (1) the method of society around the mountain adopted to potential marginal area, and giving response to others development sector as tourism and land transportation around; (2) this research hopefully will help the local government to solve the problem of development, such as planning system, research and development. The method of this research is agro-ecosystem analysis. The result shows that the people composition according to age group is highly concentrated between 18 and 47 years old and 14.339 people (49%) is as productive manpower, 71.91% is as farmer which can be classified as farmer owner land about 4.499 people (30,93%), and farmer worker 4.506 people (30,98%). Seemingly, 71.91% of people depend on farming in order to fulfill their living needs. The land area that relevant for development society partnership consist of (1) Pilot Project Unit of Usaha Pelestarian Sumber daya Alam/Usaha Pertanian Menetap (UP-UPSA/UPM); (2) Development of Hutan Rakyat (HR); (3) Hutan Rakyat dengan pola Agroforesty (HRA); (4) Kebun Rakyat (KR); (5) Budidaya Tanaman di Bawah Tegakan (BTBT); (6) Persuteraan Alam (PA);(7). Rehabilitasi Mangrove (hutan bakau); (8) Perlebahan.